Capivasertib enhances chimeric antigen receptor T cell activity in preclinical models of B cell lymphoma - Hui-Ju Hsieh; Ryan Urak; Mary C. Clark; Larry W. Kwak; Stephen J. Forman; Xiuli Wang (Molecular Therapy: Methods & Clinical Development)
Phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling is involved in the growth of normal and cancer cells and is crucial for T cell activation. Previously, we have shown that AKT Inhibitor VIII, a selective AKT-1/2 inhibitor, during chimeric antigen receptor (CAR) T cell manufacturing, improves CAR T cell function in preclinical models. Although AKT Inhibitor VIII could enhance CAR T cell function, AKT Inhibitor VIII is not a clinical-grade compound. However, pan-AKT inhibitors have been applied against cancers with PIK3CA/AKT/PTEN alterations in clinical trials. We evaluated ex vivo and in vivo strategies of enhancing CAR T cell therapeutic effect using the pan-AKT inhibitor capivasertib. We found that ex vivo 0.25 μM capivasertib treatment during the period of T cell stimulation during manufacture enhanced the antitumor activity of CAR T cells in B cell lymphoma mouse models. Mechanistically, capivasertib changed gene and protein expression patterns related to the functions of memory and effector CAR T cells. Furthermore, in vivo combination therapy of capivasertib and CD19-specific CAR T cells led to improved early response to and persistence of functional CAR T cells in mice bearing PTEN-deficient lymphoma cells compared to CAR T cells alone. Capivasertib exerts a similar function to AKT Inhibitor VIII in modulating CAR T cells, and combining CAR T cell therapy with capivasertib both ex vivo and in vivo offers the potential to improve patient outcomes. Since PTEN deficiency is common in cancer and is the main mechanism for capivasertib function, combination therapy may provide an alternative solution for the challenges of CAR T cell therapy.